Biostimulant Potential of Scenedesmus obliquus Grown in Brewery Wastewater - Navarro-López, Elvira; Ruíz-Nieto, Angela; Ferreira, Alice; Acién, F. Gabriel; Gouveia, Luisa (Molecules (Basel, Switzerland), 2020)
Microalgae are microorganisms with the capacity to contribute to the sustainable and healthy food production, in addition to wastewater treatment. The subject of this work was to determine the potential of Scenedesmus obliquus microalga grown in brewery wastewater to act as a plant biostimulant. The germination index of watercress seeds, as well as the auxin-like activity in mung bean and cucumber, and in the cytokinin-like activity in cucumber bioassays were used to evaluate the biostimulant potential. Several biomass processes were studied, such as centrifugation, ultrasonication and enzymatic hydrolysis, as well as the final concentration of microalgal extracts to determine their influence in the biostimulant activity of the Scenedesmus biomass. The results showed an increase of 40% on the germination index when using the biomass at 0.1 g/L, without any pre-treatment. For auxin-like activity, the best results (up to 60% with respect to control) were obtained at 0.5 g/L of biomass extract, after a combination of cell disruption, enzymatic hydrolysis and centrifugation. For cytokinin-like activity, the best results (up to 187.5% with respect to control) were achieved without cell disruption, after enzymatic hydrolysis and centrifugation at a biomass extract concentration of 2 g/L.